J. Grušas' Short Stories - Stonys, Juozas (Literatūra, 1970)
J. Grušas is a prominent Lithuanian prose-writer and dramatist. The article deals only with his short stories. It begins with a brief review of his first book of stories „Ponia Bertulienė" (1928). These works cannot be considered as ripe. The author of the article attaches special attention to J. Grušas' next book of short stories "Sunki ranka" (1937). The book presents many interesting features of J. Grušas' artistic originality. Some of these stories can be treated as masterpieces and they show distinctly J. Grušas' great skillfulness in literary composition. The writer takes a very keen interest in human psychology. In his best stories man is treated as a being with a very complicated inner life. His personages often act under the influence of a fit of passion. He likes to describe the moments of the highest strain of emotions. With a great skill he also reveals the rise of thoughts and feelings, their development, analyses the processes of human mind. Therefore the psychological analysis can be regarded as a distinguished feature of J. Grušas' works. The article is devoted mainly to the description of the peculiarities of this analysis.J. Grušas' recent book of stories "Rūstybės šviesa" (1969) may be regarded as an event in the literary development of the writer as well as in the nowadays Lithuanian fiction. New stories by J. Grušas are notable for their original interpretation of present life, for their interest in human existence. The structure of the new stories differs greatly from that of J. Grušas' early works of the same genre. Now the writer pays less attention to the description of everyday life. There is more generalization in the new book than in his previous works. J. Grušas is treating man as a being of deep inner contradictions. For revealing his views on life and man the writer often makes use of symbols, paradoxes and grotesque.
Keywords: -